Identification of Postoperative Step-Offs and Gaps With Brodén's View Following Open Reduction and Internal Fixation of Calcaneal Fractures. (July 2019) - Looijen, Rosalie C.; Misselyn, Dominique; Backes, Manouk; Dingemans, Siem A.; Halm, Jens A.; Schepers, Tim
Background: To date, there is no consensus regarding which postoperative imaging technique should be used after open reduction and internal fixation of an intra-articular calcaneal fracture. The aim of this study was to clarify whether Brodén's view is sufficient as postoperative radiologic examination to assess step-offs and gaps of the posterior facet. Methods: Six observers estimated the size of step-offs and gaps on Brodén's view in 42 surgically treated intra-articular calcaneal fractures. These findings were compared to postoperative CT scans (gold standard). Inter- and intraobserver reliability were calculated and compared using intraclass correlation coefficients (ICCs). Results: An accuracy of approximately 75% for both step-offs and gaps was found in foot and ankle experts. Less experienced observers correctly identified step-offs and gaps in approximately 62% of cases on fluoroscopy and in 48% on radiographs. Interobserver reliability for intraoperative fluoroscopy as well as postoperative radiographs was fair for step-offs, whereas interobserver reliability for gaps was excellent. Intraobserver reliability showed a low level of agreement for intraoperative fluoroscopy, in contrast to postoperative radiographs with excellent agreement for step-offs and good agreement for gaps. Conclusion: Our results show that especially for more experienced foot and ankle surgeons, in the majority of fractures, Brodén's view accurately showed step-offs and gaps following open reduction and internal fixation. Interobserver reliability showed a fair level of agreement for step-offs and excellent agreement for gaps. Intraobserver reliability was only enough for radiographs, not for fluoroscopy. Level of Evidence: Level IV, case series.